Latvijas trauksmes cēlāju Likumprojekta atbilstība trauksmes cēlāju jēdziena izpratnei Eiropas Padomē - Meļņika, Madara (Latvijas Universitāte, 2016)
Ir atzīts, ka trauksmes celšana ir viens no visefektīvākajiem veidiem, kā atklāt korupciju un nopietnus pārkāpumus un cīnīties pret tiem, kā arī veicināt pārredzamību, atvērtību un atbildību valsts iestādēs un privātos uzņēmumos. Tomēr efektīvas aizsardzības neesamība var radīt dilemmu starp sabiedrības interesēm un pašas personas vēlmi būt drošībā un saglabāt savu līdzšinējo darba vietu un stāvokli tajā. Autore darbā analizē šībrīža trauksmes cēlēju aizsardzību Latvijā un sniedz atzinumus par Latvijas Trauksmes cēlēju likumprojektu un citu Eiropas Padomes valstu likumiem. Rezultātā izveidoti ierosinājumi Likumprojekta jaunai redakcijai, kas atbilstu Eiropas Padomes Rekomendācijai CM/Rec(2014)7 un cilvēktiesību standartiem, tādējādi nodrošinot pienācīgu trauksmes cēlēju aizsardzību un iedrošinot celt trauksmi.

Whistleblowing is one of the most effective ways to detect corruption and serious irregularities and fight against them, as well as to promote transparency, openness and accountability of public institutions and private enterprises. However, the absence of effective protection may create a dilemma between the public interests and the person's own will to be safe and keep their current job. The author analyzes the current protection of whistleblowers in Latvia and delivers the opinion on the Draft Law on Protection of Whistleblowers and the laws of other analysed Council of Europe countries. As a result, there are created proposals for the Draft Law for it to be in line with Council of Europe Recommendation CM/Rec (2014)7 and the human rights standards, thus ensuring a proper whistleblower protection and encouraging whistleblowing. Whistleblowing is one of the most effective ways to detect corruption and serious irregularities and fight against them, as well as to promote transparency, openness and accountability of public institutions and private enterprises. However, the absence of effective protection may create a dilemma between the public interests and the person's own will to be safe and keep their current job. The author analyzes the current protection of whistleblowers in Latvia and delivers the opinion on the Draft Law on Protection of Whistleblowers and the laws of other analysed Council of Europe countries. As a result, there are created proposals for the Draft Law for it to be in line with Council of Europe Recommendation CM/Rec (2014)7 and the human rights standards, thus ensuring a proper whistleblower protection and encouraging whistleblowing.
The compliance of the Dreft Law on the Protection of Whistle blowers of Latvia with the definition of whistleblowers in the Council of Europe
Keywords: Juridiskā zinātne; trauksmes celšana; vārda brīvība; likumprojekts; sabiedrības intereses; Eiropas Padome